Планування фонду оплати праці на підприємстві - Пивоваров, М. О. (ХНУРЕ, 2025)
At the current stage of economic development, there are many obstacles that complicate the effective operation of enterprises and slow down the reform process. One of these problems is the irrational use of the wage fund. In market conditions, when the main goal of the enterprise is to obtain maximum profit, the importance of planning labor costs becomes obvious. The change in economic conditions and the introduction of the latest technologies form new requirements for the management of the wage fund, focusing on ensuring the motivation of employees and increasing the efficiency of their work. The experience of other countries shows that the successful management of these costs is one of the determining factors for the long-term development of enterprises.
Keywords: оплата праці; фонд оплати праці